PROSEDUR PEMASUKAN DATA WAKTU LEMBUR DENGAN SISTEM POIS DI PT PERTAMINA GAS - Juwairiah, Nafizah; Jati Saputro, Restu; Mustofa, Anwar (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
: In the era of technology, the advancement of technology and information has opened up new opportunities for companies to enhance efficiency in Human Resource Management. To continuously optimize operational management, PT Pertamina Gas is comprehensively committed to strengthening efficiency aspects, particularly in the Human Capital and Business Support sectors. Understanding the crucial role of these aspects in operational success, PT Pertamina Gas has introduced a revolutionary innovative system known as Pertagas Outsourcing Information System or POIS. POIS is not just an acronym for Pertagas Outsourcing Information System, but it is a leading solution designed with the primary goal of streamlining and simplifying the information management process related to the overtime work of partners or outsourced workers. This system serves as a solid foundation that supports operational effectiveness, especially in terms of reporting information for workers involved in routine overtime activities. The data collection method used in this research is interviews by posing questions related to the field being studied. The results of this research are related to the procedure of overtime filling through the POIS system.